Comparative study of signal loss and reflection in bent optical fibers and their impact on radiodirection-finding systems - Tuleshov, Amandyk; Abdykadyrov, Askar; Ualiyev, Zhomart; Eshmagambetova, Sandugash; Ismailova, Zukhra (International Journal of Innovative Research and Scientific Studies, 2025)
This research focuses on a comprehensive assessment of the impact of signal loss and reflection in bent optical fibers on the accuracy of radiodirection - finding systems. The relevance of the problem lies in the signal distortions that occur due to the integration of optical and radio frequency components in 5G/6G infrastructures, which can lead to navigation errors. During the study, signal attenuation and reflection under various bending radii and configurations were numerically modeled using COMSOL, MATLAB, and Python platforms. According to the results, when the bending radius is less than 10 mm, signal loss reaches up to 3.8 dB/km, and the direction-finding error increases up to 6.7%. These distortions are explained by phase shift and modal losses. The findings enable the adoption of practical engineering solutions, particularly for the correct design of optical networks in radionavigation systems. The proposed models and technical recommendations are of practical importance for the development of modern high-precision direction-finding systems.